The prevalence of disordered eating attitude and its relation to exercise participation in a sample of physical education students - Rouzitalab, Tohid; Gargari, Bahram Pourghassem; Izadi, Azimeh; Amirsasan, Ramin; Azarmanesh, Deniz; Jafarabadi, Mohammad Asghari (Progress in Nutrition, 2019)
Background: It has been shown that sport and physical activity in order to obtain an ideal body shape constitute the major risk factors for the development of eating disorders. The aim of this study was to examine the physical activity scores differences among students with disordered eating attitudes and the healthy physical education students. Methods: This cross-sectional study was conducted on 210 physical education students, 105 males, and 105 females aged 18 to 25 years old who were selected by systematic random sampling from the physical education school at Tabriz University in Tabriz, Iran in 2013. Eating Attitude Test (EAT-26) was used for assessment of disordered eating attitudes. Physical activity score was calculated using MET questionnaire. In addition, demographic characteristics were examined. Results: About 10% of studied subjects had disturbed eating attitudes and the disordered eating attitude, defined as EAT-26 ≥ 20, was significantly more common among males (15.4%) compared to females (4.8%) (P<0.05). The physical activity scores were 46.50 ± 5.99 and 45.71 ± 5.23 (MET.h/day) for men and women, respectively. In studied subjects, physical activity scores were significantly different when comparing participants with disordered eating attitudes and the healthy group (P<0.001). Conclusion: Abnormal-eating attitude is more common among male physical education students than female physical education students in Tabriz, Iran. It seems that compulsive physical activity is related to the disordered eating attitudes.